Alasan Uni Eropa Menetapkan Kebijakan Renewable Energy Directive II Terhadap Impor CPO Indonesia Tahun 2018 - Ari Winanda, I Gusti Agung Bagus; Rainy Priadarsini, Ni Wayan; Widya Nugraha, A. A Bagus Surya (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2022)
This research aims to describe the reason the European Union set biofuel policy through renewable energy directive (RED II) against crude palm oil (CPO) imports from Indonesia in 2018. CPO has grown in dominating the EU biofuel industry used as biodiesel raw materials. However, since 2018 the European Union decided to implement RED II as a policy with sustainability criteria that regulate biofuel utilization procedures especially biodiesel. This research is analyzed using descriptive qualitative research methods with secondary data collection focusing on state level analysis. The theoretical framework in this research used the concepts of Protectionism and Green Protectionism. This research found that the EU's decision to set a RED II policy towards Indonesia's CPO imports could protect the biofuel industry in the European Union. Keywords : Crude Palm Oil, Renewable Energy Directive, Protectionism, Green Protectionism.